Use of ammunition with programmable blasting time in air-defense complex - В.В. Воїнов (Наука і техніка Повітряних Сил Збройних Сил України)
The rapid spread and wide availability of unmanned aerial vehicle technologies creates a new type of airborne threat - massive and cheap strike and reconnaissance drones. It creates the new challenges for the army and objects air defense - improving the accuracy of air targets hitting and reducing the cost of ammunition. In article analysis of increasing the possibilities of the small air targets defeating by the available air defense means was done. A significant increase in the efficiency of hitting targets supposed to get by existing anti-aircraft artillery with help by the use of ammunition with programmable blasting time. A number of measures have been proposed to improve existing air defense facilities to enable them to use such type of ammunition.